Application of a modified mean-field method to a gauge-invariant variational calculation - Omero, C.; Della Selva, A.; Deza, R. J.; Parga, N.O.; Másperi,Luis (American Physics Society, 1982)
Fil: Omero, C. Comisión Nacional de Energía Atómica; Argentina